Paleodiet and health in a mass burial population: The stable carbon and nitrogen isotopes from Potočani, a 6, 200‐year‐old massacre site in Croatia. (28th July 2020) - McClure, Sarah B.; Zavodny, Emily; Novak, Mario; Balen, Jacqueline; Potrebica, Hrvoje; Janković, Ivor; Kennett, Douglas J.
Abstract: This paper presents the results of carbon and nitrogen stable isotope analyses on human remains uncovered from Potočani, a Copper Age (Eneolithic) mass burial site in continental Croatia. The remains of at least 41individuals were uncovered in a pit in 2007 during rescue excavations in Požeško‐Slavonska county. Skeletal evidence of violence and the disorganized arrangement of bodies suggest that burial took place over a short period of time. Radiocarbon dates and associated ceramics indicate these people were part of the Lasinja cultural group, dating to the Middle Copper Age (ca.4200 cal BC). Carbon and nitrogen stable isotope analyses on 40individuals indicate higher than expected nitrogen values in comparison with other regional populations and significant differences between children, juveniles, and adults at the site of Potočani. Bioarchaeological and stable isotope results support the interpretation that the people buried at Potočani likely experienced dietary stress in the years leading up to their violent deaths.